British Library Dataset Programme: Supporting Research in the Library of the 21st Century - Max Wilkinson, J.; Pollard, Tom; Farquhar, Adam (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
Advances in computational science and its application are reshaping the social landscape and the practice of research. Researchers are increasingly exploiting technology for collaborative, experimental and observational research in all disciplines. Digital data and datasets are the fuel that drives these trends; increasingly datasets are being recognised as a national asset that requires preservation, attribution and access in much the same way as text-based communication. The British Library is in a unique position to enhance UK and international research by extending its presence from the physical collection to the digital dataset domain. To meet this challenge and be a responsible steward of the scholarly record, the Library has defined a programme of activity to support the datasets that underlie modern research and promote them as a national asset. We are designing a mixed model of activity where specific service-level projects with clear goals will provide support for collaborative work aimed at revealing and clarifying requirements related to datasets. For example, there is a clear community need for stable, scalable and agreed data citation mechanisms. In response the British Library became a founding member of DataCite, the International Data Citation Initiative which, as a member of the International DOI foundation, assigns Digital Object Identifiers (DOIs) to datasets. We are leveraging the services built for DataCite to actively partner with a number of UK data centres and data publishers to add value to their collections and facilitate the rejoining to the scholarly record by linking the published record with the datasets that underlie it. We are also implementing a similar strategy to promote dataset discovery services through the Library’s catalogues and streamlining access to national external collections. The British Library datasets programme will guide activities across the Library and provide a focus for stakeholder communities to address the challenge of integrating datasets into their researcher services. This work will ensure that the integrity of the scholarly record remain intact, useable and vital for future generations.